قضية في طباعة المصاحف القرآنية: الخلاف في علم العدد وتطبيقه في طباعة المصاحف القرآنية في العالم - Abd Muhaimin Ahmad,; Sabri Mohamad,; Haziyah Hussin, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
The science of `adad constitutes an integral part of Quranic-affiliated knowledge. Its main discussion is about the beginning and ending of the verse of the Quran as well as distinction numbering of the verses. There are seven famous opinions in `adad, namely; Madani Awwal, Madani Akhir, Makki, Kufi, Basri, Shami and Himshi. The difference of opinions in the determination of Quranic verses does not only affect the calculation of the total number of verses in the Qur'an, but also contribute to the differences in the nature of mushaf (printed Quran). This is because the scholars have variant views on determining the madhdhab (opinion) of ‘adad relied upon by some qiraat mutawatirah and its riwayah. Thus, this study explores and gathers the views of the scholars in determining the madhdhab (opinion) for respective qiraat mutawatirah, and identify their justifications. This study will then examine the effect of the dispute on mushaf Quran. To achieve the aforementioned objectives, content analysis method was adopted to bring together the views of scholars in determining opinions for each qiraat mutawatirah, and to analyze descriptively the narrations of all opinions to explain the cause of the disagreement among the scholars. In order to know the impact of the differences in `adad on mushaf Quran, induction methods was used on the mushaf Quran which has been printed in several countries with distinctive qiraat mutawatirah. This study finds that the sanad (chain of transmitter) in narrating `adad forms is the contributing factor in dissenting scholars in determining credible opinion for each qiraat mutawatirah. In regards to the printing of mushaf, most of the printed mushafs are aligned with the opinion of scholars in determining the number of the verses, whereas only a few of mushaf which do not comply with such opinion.